Association between rainfall seasonality and the flowering of epiphytic plants in a Neotropical montane forest - Cascante Marín, Alfredo (2017)
The association between the reproductive phenology of epiphytic communities with environmental and ecological factors remains largely unexplored. Because epiphytes depend on environmental moisture, seasonal changes in moisture conditions likely act as the primary determinants of their reproductive timing. We examined whether water limitation or pollinator competition structures the flowering phenologies of an epiphytic community in a seasonal mountain forest in Costa Rica. Additionally, we addressed the environmental factors that might trigger floral induction. Using a 24‐month dataset of bimonthly flowering records from 104 species, we found high seasonality of flowering at the species level but somewhat lower seasonality at the community level. The flowering mid‐dates of most epiphytes, particularly from monocotyledonous species, occurred during the wettest months, as predicted if water limitation structures flowering. The increased moisture and nutrient availability during the rainy season give epiphytes the resources needed to complete floral development and anthesis, and later fruit and seed maturation. The observed flowering pattern of epiphytes coincides with reproductive patterns of terrestrial herbs and shrubs from seasonal tropical ecosystems, and suggests shared constraints to sexual reproduction in both ecological guilds under similar climatic conditions. In contrast, flowering patterns of congeneric epiphytes in the same pollination guild mostly did not follow the expectations of a pollinator competition scenario. Finally, we discuss the possible combined effect of precipitation, temperature, and daily insolation on floral induction of epiphytic plants.